ISAAC AND THE WELL OF GERAR IN THE LIGHT OF ARCHAEOLOGICAL EVIDENCE - Ndishua, Julius (International Journal of Culture and Religious Studies, 2022)
This article focuses on Isaac and the well of Gerar in the light of archaeological evidence. In the Old Testament, Well-Water was one of the primary sources alongside "˜springs', "˜rainfall', "˜dew', "˜streams' and "˜cisterns'. Today, the digging of boreholes for private and public consumption is similar to the idea of wells in the ancient Near East. The fundamental question is: is there archaeological evidence that supports the life and culture of the Patriarchs in the ancient Near-East, the excavation of Gerar and the evidence of wells? This research aims to examine the life of Isaac and the well of Gerar in light of archaeological evidence. The researcher used the bibliographical historical research method to evaluate facts. The findings revealed that the Nuzi, Mari, and Ebla tablets are significant archaeological discoveries that support the Patriarchs' life and culture. Isaac the Patriarch was an actual figure who lived at Beersheba and Gerar from the excavation expeditions. He dug wells for domestic use and for his cattle that brought about conflict between him and the people at Gerar. Besides, Isaac serves as an exemplary leader in conflict resolution. He did not fight back or hire men to fight for him when confronted; instead, he resolved the conflict faced at Gerar peacefully. Thus, in the light of archaeological evidence, Isaac the Patriarch serves as an exemplary leader for everyone to emulate in a hostile environment.